Association Between Housing Items and Amenities With Psychological Wellbeing, and Their Possible Impact on All-Cause and Cardiovascular Mortality Risk in Lithuania - Dalia Luksiene; Abdonas Tamosiunas; Giedre Aukstakalniene; Svitlana Boieva; Ricardas Radisauskas; Martin Bobak (Frontiers Media S.A., 2024)
ObjectivesTo determine the association of housing items and amenities with psychological wellbeing (PWB) and their relationship with all-cause and cardiovascular disease (CVD) mortality.MethodsThis study was based on the framework of the HAPIEE study. Data from the Lithuanian Mortality Register were used to evaluate CVD and all-cause mortality from baseline survey (2006-2008) till 2023. The logistic regression model and multivariate Cox regression model were applied for data analysis.ResultsThe multivariable regression models showed that the material aspects of people's lives influenced their PWB status: increasing the number of housing items per 1 unit significantly increased the odds ratio (OR) of higher PWB status for males [OR = 1.14 (95% CI 1.11-1.18)] and females [OR = 1.13 (95% CI 1.11-1.17)] and decreased the risk of all-cause and CVD mortality in females [respectively HR = 0.93 (95% CI 0.91-0.96) and HR = 0.91 (95% CI 0.87-0.95)] and in males [respectively HR = 0.92 (95% CI 0.90-0.94) and HR = 0.90 (95% CI 0.87-0.93)].ConclusionThese data suggest that the household items and amenities influenced PWB and may be used as risk factors in assessing the risk of all-cause and CVD mortality.